(untitled) (Eurasian Medical Research Periodical, 2026)
Gastroesophageal reflux disease (GERD) is among the most common gastrointestinal disorders and represents an important risk factor for esophageal adenocarcinoma [4,8]. Dysfunction of the lower esophageal sphincter (cardia insufficiency) plays a central role in its development. Long-term exposure of the esophageal mucosa to gastric acid and bile acids leads to chronic inflammation, oxidative stress, and accumulation of genetic alterations, which may ultimately result in malignant transformation [7,12]. This paper reviews current data on the sequence of morphological changes, molecular mechanisms of carcinogenesis, and clinical implications for surveillance